Transitioning to Life in a Nursing Home: The Potential Role of Palliative Care. Issue 1 (January 2021) - Halifax, Elizabeth; Bui, Nhat Minh; Hunt, Lauren J.; Stephens, Caroline E.
Background and Objectives: Transitioning to a nursing home (NH) is a major life event for 1.4 million NH residents in the United States. Most post-acute NH admissions plan for rehabilitation and discharge home, but with nearly 70% of NH residents being palliative care (PC) eligible, many evolve into long-term placements secondary to poor health and associated decline in function and/or cognition. This article describes the perceptions of NH PC-eligible residents and families transitioning to life in a NH. Methods: Residents at 3 NHs in Northern California (N = 228) were screened for PC eligibility. A convenience sample of PC-eligible residents and their family members (n = 28) participated in qualitative interviews that explored the experience of living as a NH resident with serious illness. Data were analyzed using grounded theory methodology. Results: Our study provides insights into the experiences of transitioning to a NH from the perspectives of PC-eligible residents and their families. These data describe how PC-eligible residents and their families experienced disempowerment as they perceived being left out of decisions to go to a NH, loss of autonomy once at the NH, dealt with the realization that they would not be going home, and described perceived barriers to going home. Discussion and Implications: The inclusive and person-centered model of care that PC provides naturally empowers residents and family members. Adequate provision of PC services, together with changes in policy related to NH culture and benefit management, could improve the experience of transitioning to a nursing home.